Safety and Performance of a New Burr Hole Covering Device: Results of the Multicenter COVER Registry - Asencio-Cortés, Carlos; Villalba, Gloria; De Vilalta, Álex; Serrano, Laura; Álvarez-Holzapfel, María Jesús; Montes-Graciano, Guillermo; Málaga, Xavier; Muñoz-Hernandez, Fernando; Gabarrós, Andreu (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background Burr hole covering in brain surgical procedures can avoid complications and unaesthetic results. The aim of this registry was to assess the safety and performance of a new polymeric burr hole covering device (Cranial COVER, NEOS Surgery).Methods A multicenter, prospective, clinical registry design was used for the study. All the patients who fulfilled the inclusion criteria were included in the study and followed up for 6 months. Baseline clinical parameters, surgical variables (technical success of the implantation, surgeon satisfaction), postoperative variables (aesthetic and functional results, neuroimaging artifacts), and adverse events were evaluated.Results Forty-three Cranial COVER devices were implanted in 30 patients. Most of them were implanted in frontal locations (53.5%). After implantation, 97.7% of the devices completely covered the burr hole, and 100% perfectly adapted to the skull surface. All surgeons ranked their satisfaction with the implantation procedure as very high or high. No artifacts were detected in any of the neuroimaging studies performed and no adverse events related with the device or its implantation were reported during the follow-up. There were significantly more scalp depressions associated with uncovered than with Cranial COVER–covered burr holes (p = 0.040). Patient satisfaction with covered burr holes located in the frontal and parietal areas was 9.0 ± 1.4 over 10.Conclusion Cranial COVER is a safe and reliable burr hole covering system that offers excellent cosmetic results and high satisfaction rates for both surgeons and patients. Cranial COVER is highly adaptable to the skull surface, and it was predominantly used in frontal locations due to their cosmetic importance.
Keywords: craniotomy; implant; polyether ether ketone; trephining